Decidual relaxins: Gene and protein up-regulation in preterm premature rupture of the membranes by complementary DNA arrays and quantitative immunocytochemistry - Tashima, Lily S.; Yamamoto, Sandra Y.; Yasuda, Maaya; Millar, Lynnae K.; Bryant-Greenwood, Gillian D. (American journal of obstetrics and gynecology, 2002)
Objective: This study was undertaken to show both decidual relaxin gene and protein up-regulation in preterm premature rupture of the fetal membranes. Study Design: Membranes after preterm premature rupture (n = 4) have been matched in pairs with preterm intact membranes (n = 4). These tissues were from patients without infection, labor, preeclampsia or intrauterine growth restriction, and none of the patients had a latency period of more than 8 hours. The messenger RNAs from these tissues were used on complementary DNA expression arrays; 488 genes were analyzed. Relaxin gene expression was quantitated from the arrays and in additional tissues by Northern analysis. The two relaxin proteins, H1 and H2, in the decidual cells were immunolocalized and quantitated by microdensitometry with the use of specific antisera that were raised to decapeptides over the region of least homologic features. The expression of five other genes that were selected from the arrays were quantitated by Northern analysis. Results: Relaxin gene expression was up-regulated 3.4-fold on the complementary DNA arrays but was not confirmed on Northern analysis. On the other hand, protein analysis for relaxin H1 and H2 in the decidual cells showed them to be significantly up-regulated (P <.0001, for both proteins) in patients with preterm premature rupture of the membranes compared with control subjects. The 20 most highly expressed genes at preterm in tissues without rupture were determined. In addition, analysis of the genes that were up-regulated with preterm rupture of the membranes showed 30 differentially expressed genes. Conclusion: Relaxin gene expression in the decidua is up-regulated, and its protein expression is significantly increased with preterm rupture of the fetal membranes. (Am J Obstet Gynecol 2002;187:785-97.)